Eco-Deconstruction Derrida and Environmental Philosophy - Fritsch, Matthias; Lynes, Philippe; Wood, David (Groundworks: Ecological Issues in Philosophy and Theology, 2018)
Eco-Deconstruction marks a new approach to the degradation of the natural environment, including habitat loss, species extinction, and climate change. While the work of French philosopher Jacques Derrida (1930–2004), with its relentless interrogation of the anthropocentric metaphysics of presence, has already proven highly influential in posthumanism and animal studies, the present volume, drawing on published and unpublished work by Derrida and others, builds on these insights to address the most pressing environmental issues of our time.The volume brings together fifteen prominent scholars, from a wide variety of related fields, including eco-phenomenology, eco-hermeneutics, new materialism, posthumanism, animal studies, vegetal philosophy, science and technology studies, environmental humanities, eco-criticism, earth art and aesthetics, and analytic environmental ethics.